Computer Usage and Labour Regulation in India's Retail Sector - Amin, Mohammad (2012)
A recent survey of 1,948 retail stores in India conducted by the World Bank's Enterprise surveys shows that 19 per cent of all stores use computers. In the state of Kerala, the figure is as high as 40 per cent. Using this survey, we estimate the effect of computer usage on labour employment. Our findings show that this effect depends on the stringency of the underlying labour laws. Stricter labour laws magnify the labour displacing effect of computers significantly.